Hydromagnetic acceleration in relativistic outflows - Vlahakis, Nektarios (2003)
We demonstrate that hydromagnetic acceleration can be the driving mechanism of relativistic outflows in AGNs as well as in Gamma-ray burst sources and Crab-like pulsars. Using semianalytical solutions of the full set of the steady, axisymmetric, ideal hydromagnetic equations in flat spacetime—i.e., solving the momentum equation along the flow as well as in the transfield direction—we model the acceleration of relativistic outflows. We find that a Poynting-flux dominated flow near the source reaches equipartition between matter and magnetic energy-fluxes, or even becomes completely matter-dominated (as in the case of Crab-like pulsar winds).